Calm on the surface, dynamic on the inside. Molecular homeostasis of Anabaena sp. PCC 7120 nitrogen metabolism. (3rd March 2021) - Perin, Giorgio; Fletcher, Tyler; Sagi‐Kiss, Virag; Gaboriau, David C. A.; Carey, Mathew R.; Bundy, Jacob G.; Jones, Patrik R.
Abstract: Nitrogen sources are all converted into ammonium/ia as a first step of assimilation. It is reasonable to expect that molecular components involved in the transport of ammonium/ia across biological membranes connect with the regulation of both nitrogen and central metabolism. We applied both genetic (i.e., Δamt mutation) and environmental treatments to a target biological system, the cyanobacterium Anabaena sp PCC 7120. The aim was to both perturb nitrogen metabolism and induce multiple inner nitrogen states, respectively, followed by targeted quantification of key proteins, metabolites and enzyme activities. The absence of AMT transporters triggered a substantial whole‐system response, affecting enzyme activities and quantity of proteins and metabolites, spanning nitrogen and carbon metabolisms. Moreover, the Δamt strain displayed a molecular fingerprint indicating nitrogen deficiency even under nitrogen replete conditions. Contrasting with such dynamic adaptations was the striking near‐complete lack of an externally measurable altered phenotype. We conclude that this species evolved a highly robust and adaptable molecular network to maintain homeostasis, resulting in substantial internal but minimal external perturbations. This analysis provides evidence for a potential role of AMT transporters in the regulatory/signalling network of nitrogen metabolism and the existence of a novel fourth regulatory mechanism controlling glutamine synthetase activity. Abstract : The nitrogen‐metabolism of Anabaena sp. PCC 7120 was perturbed by the deletion of the amt operon encoding ammonium uptake transporters, resulting in minimal phenotypic change compared to wild‐type, under varying environmental conditions. In contrast, targeted molecular systems analysis (proteins, enzymes and metabolites) indicated substantial re‐arrangement of both nitrogen and carbon metabolisms. The work illustrates the complex response required to achieve homeostasis and suggests AMT proteins might have a role in the regulatory/signalling network of nitrogen metabolism.